2022
DOI: 10.1038/s41385-022-00494-y
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial GPR35 protects from Citrobacter rodentium infection by preserving goblet cells and mucosal barrier integrity

Abstract: Goblet cells secrete mucin to create a protective mucus layer against invasive bacterial infection and are therefore essential for maintaining intestinal health. However, the molecular pathways that regulate goblet cell function remain largely unknown. Although GPR35 is highly expressed in colonic epithelial cells, its importance in promoting the epithelial barrier is unclear. In this study, we show that epithelial Gpr35 plays a critical role in goblet cell function. In mice, cell-type-specific deletion of Gpr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…A recent study shows that loss of forkhead box O 1( Foxo1 ) in intestinal epithelial cells results in defects in goblet cell autophagy and mucus secretion, which induces gut dysbiosis, disruption of gut barrier integrity, and increased susceptibility to intestinal inflammation 99 . Deficiency G protein-coupled receptor 35 ( Gpr35 ), previously known to regulate the activity of Na/K-ATPase and mitochondrial oxidative phosphorylation (OXPHOS) of epithelial cells 100 , was recently shown to induce goblet cell depletion and dysbiosis 101 , 102 . Interestingly, ablation of Calcitonin gene-related peptide ( Cgrp ) in nociceptor neurons or epithelial Ramp1 is also shown to reduce goblet cell mucus secretion, which induces dysbiosis and susceptibility to colitis 103 .…”
Section: Mechanisms Underlying Host Genetics-induced Gut Microbial Re...mentioning
confidence: 99%
“…A recent study shows that loss of forkhead box O 1( Foxo1 ) in intestinal epithelial cells results in defects in goblet cell autophagy and mucus secretion, which induces gut dysbiosis, disruption of gut barrier integrity, and increased susceptibility to intestinal inflammation 99 . Deficiency G protein-coupled receptor 35 ( Gpr35 ), previously known to regulate the activity of Na/K-ATPase and mitochondrial oxidative phosphorylation (OXPHOS) of epithelial cells 100 , was recently shown to induce goblet cell depletion and dysbiosis 101 , 102 . Interestingly, ablation of Calcitonin gene-related peptide ( Cgrp ) in nociceptor neurons or epithelial Ramp1 is also shown to reduce goblet cell mucus secretion, which induces dysbiosis and susceptibility to colitis 103 .…”
Section: Mechanisms Underlying Host Genetics-induced Gut Microbial Re...mentioning
confidence: 99%
“…11 However, 1-acyl and 2-acyl LPA did not induce receptor internalization or GPR35-dependent migration in WEHI-231 cells, 9 and in contrast to a synthetic GPR35 agonist, LPA had little effect on GPR35 + goblet cells. 32 An added challenge in making definitive statements about new LPA ligand-receptor relationships is the widespread expression of six established LPA receptors and the need to rule out their involvement. 33 Returning to KynA, early work showed it induced a robust Ca 2+ response and [ 35 S] GTPγS incorporation in membrane preparations from CHO-GPR35 cells 10 and later work showed induction of cell adhesion and migration in vitro.…”
Section: Gpr35 Activation Can Be Qualitatively Distinct and Cell Type...mentioning
confidence: 99%
“…115 As noted above, the microbiome may also be a diet-influenced source of 5-HIAA. 54 Most recently, Melhem et al 32 found that epithelial GPR35 expression in the intestine was highest in goblet cells in the proximal colon. GPR35-deficiency in epithelial cells led to increased pyroptosis of proximal colon goblet cells, reduced mucin production and more proximal association of bacteria with the colon.…”
Section: G Pr35 Fun C Ti On S In Other Tissue Smentioning
confidence: 99%
“…The translocated intimin receptor of enteropathogenic Escherichia coli triggered rapid Ca 2+ influx in IECs, which induced LPS internalisation, resulting in the activation of caspase-4/GSDMD-driven pyroptosis of IECs (75). Melhem et al (76) found that epithelial G protein-coupled receptor 35 protected against Citrobacter rodentium infection through guarding goblet cells from dysregulated caspase-11/GSDMD-mediated pyroptosis and maintaining mucosal barrier integrity. The canonical NLRP3/caspase-1/GSDMD pathway-dependent pyroptosis in macrophages contributed to the immunopathology and innate inflammatory responses upon gastrointestinal norovirus infection (77).…”
Section: Gasdermins-mediated Lytic Cell Death In Enteropathogenic Mic...mentioning
confidence: 99%